(untitled) - Shida, Eiichiro (Honolulu, 1974)
The book thus makes a unique contribution to an understanding of comparative culture, developing further the theories of the philosopher Testsuro Watsuji, as presented in his influential Fudo , and serves also as an introduction to the various studies in the social sciences pursued in postwar Japan.